Age-standardized incidence and mortality rates of oral and pharyngeal cancer in Puerto Rico and among Non-Hispanics Whites, Non-Hispanic Blacks, and Hispanics in the USA - Diaz Elba C; Hernández Eduardo Y; Calo William A; Suárez Erick; Figueroa Nayda R; Ortiz Ana P (BMC Cancer, 2009)
Abstract Background In the American region, Puerto Rico (PR) has the highest incidence of oral and pharyngeal cancer (OPC), but racial/ethnic differences have never been assessed and compared with other groups in the United States of America (USA). We compared the age-adjusted incidence and mortality rates of OPC between PR and among USA Hispanics (USH), Non-Hispanic Whites (NHW), and Non-Hispanic Blacks (NHB) to assess the burden of this cancer in PR. Methods Analysis of the age-standardized rates (per 100,000) was performed using the direct method with the world standard population (ASR(World)) from 1998–2002. Annual percent change (APC) and Relative Risks (RR) were calculated using the Poisson regression model. Results The incidence ASR(World) for men in PR was constant (APC ≈ 0.0%), in contrast, a decrease was observed among NHW, NHB, and USH men, although only USH showed statistical significance (APC = -4.9%, p < 0.05). In women, the highest increase in incidence (APC = 5.3%) and the lowest decrease in mortality (APC = -1.4%) was observed in PR. The ratio of the ASR(World) showed that in all racial/ethnic groups, men had approximately 2–4 fold increased incidence and mortality risk of OPC than women (p < 0.05). Men in PR had a higher mortality risk (p < 0.05) of OPC as compared to USH, NHW, and NHB; but among women, PR showed a significant excess of mortality only as compared to USH (est. SRR = 1.82, 95% CI = 1.41, 2.33). Conclusion The overall higher incidence of OPC in men in PR as compared to USH, NHB, and NHW could be explained by the effect of gene-environment interactions. Meanwhile, the higher mortality from OPC in PR suggests limitations in the health-care access within this population. Further research is warranted to elucidate these findings.